Infection of gnotobiotic pigs with an Escherichia coli O157:H7 strain associated with an outbreak of hemorrhagic colitis. - Francis, D H (1986)
Gnotobiotic pigs inoculated with an Escherichia coli O157:H7 strain isolated from a human with hemorrhagic colitis developed anorexia, lethargy, and watery diarrhea. Bacteria diffusely colonized the cecum and colon surfaces and the crypt epithelium. At bacterial attachment sites, microvilli were effaced, and epithelial cells were irregularly shaped, rounded, or detached. Submucosa, lamina propria, and mesentery were markedly edematous and contained many inflammatory cells.